Hydrocephalus, scoliosis, palatoschisis and arthrogryposis in a brown swiss calf - Serap Türkütanıt; Recai Tunca (Eurasian Journal of Veterinary Sciences)
Various malfonnations were defined on a dead Brown Swiss calf born by cesarean section.Significant hydrocephalus was observed in this case. Circumference of the skull and quantity of cerebrospinal fluid in ii were 93 cm. and 12 It. respectively. Also cranioschisis, scoliosis, spinal stenosis, palatoschisis and arthrogryposis were observed in the case.